Sharing Space between Secular and Religious: The Case of the St. Dumitru Romanian Orthodox Church in Upper West Side Manhattan, New York - Cozma, Ioan (Fieldwork in religion, 2024)
This article analyzes the St. Dumitru Romanian Orthodox Church in New York City's Upper West Side - a shared sacred place that blends religious, domestic, and community functions within a secular urban fabric. We explore how sacralization processes transform a former residential building into a place of worship, a home for its parish priest, and a spiritual home for its congregation. The study maps the religious geography of the neighborhood, emphasizing how private and domestic spaces become sites of religious life, thus blurring the boundaries between the secular and the sacred. Particular attention is given to the spatial negotiations that allow the coexistence of divine presence, everyday domesticity, and community participation in a single, fluid environment. Drawing on four years of participant observation (2021-2024), interviews, fieldnotes, and archival materials, as well as autoethnographic insight - given that one author serves as the church's rector - this research offers a grounded, multilayered account of religious resilience, place-making, and everyday lived religion in a diverse urban setting. We argue that such hybrid religious spaces challenge conventional distinctions between sacred and profane and suggest new methodological and theoretical directions for the study of religion in contemporary cities.